2020
DOI: 10.1097/hjh.0000000000002252
|View full text |Cite
|
Sign up to set email alerts
|

Central arterial stiffness and retinal vessel calibers: the Atherosclerosis Risk in Communities Study–Neurocognitive Study

Abstract: Background:The retinal microvasculature provides a window to the cerebral vasculature and enables examination of changes in retinal caliber that may mimic those occurring in cerebrovascular disease. The association of central arterial stiffness and retinal vessel caliber in a population sample is not fully understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
0
15
1
3
Order By: Relevance
“…In contrast to previous studies, 11 , 12 , 13 , 14 , 15 we observed no association between arterial stiffness and narrower retinal arteriolar diameters, possibly because inward remodeling (the proximate cause of arteriolar narrowing) 3 occurs in a more advanced disease stage than was present in the population that we studied. Additionally, and similar to most previous studies, 11 , 14 , 15 we observed no association of arterial stiffness with retinal venular diameters, possibly because hemodynamic stress in venules is insufficient to affect their structure.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous studies, 11 , 12 , 13 , 14 , 15 we observed no association between arterial stiffness and narrower retinal arteriolar diameters, possibly because inward remodeling (the proximate cause of arteriolar narrowing) 3 occurs in a more advanced disease stage than was present in the population that we studied. Additionally, and similar to most previous studies, 11 , 14 , 15 we observed no association of arterial stiffness with retinal venular diameters, possibly because hemodynamic stress in venules is insufficient to affect their structure.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study found increased PWV was associated with wider retinal venular caliber in the Atherosclerosis Risk in Communities Study 30 . Current guidelines by the European Society of Hypertension state that a measured PWV larger than 10 m/s can be considered an independent marker of HMOD 8 .…”
Section: Discussionmentioning
confidence: 76%
“…Микроваскулярная дисфункция служит одним из ключевых факторов патогенеза АГ. Сужение артериол и расширение венул сетчатки могут нести неодинаковую информативную прогностическую нагрузку, поэтому их дифференцированная оценка играет более значимую роль, нежели определение артериовенозного соотношения [7]. Наряду с сужением артериол сетчатки расширение венул способно независимо от других факторов коррелировать с вероятностью выявления АГ [7].…”
Section: Discussionunclassified
“…Сужение артериол и расширение венул сетчатки могут нести неодинаковую информативную прогностическую нагрузку, поэтому их дифференцированная оценка играет более значимую роль, нежели определение артериовенозного соотношения [7]. Наряду с сужением артериол сетчатки расширение венул способно независимо от других факторов коррелировать с вероятностью выявления АГ [7]. Установлено, что дилатация ретинальных венул ассоциирована с системным низкоинтенсивным воспалением, лабораторными и инструментальными маркерами атеросклероза, эндотелиальной дисфункции, фиброза и другими метаболическими отклонениями [8].…”
Section: Discussionunclassified
See 1 more Smart Citation